TiO2/SO42- Solid Superacid: A Rapid, Solventless, Recoverable Nanocatalyst for Eco-Friendly Synthesis of Piperidin-4-one Oximes - Nivetha, Narayanasamy; Thangamani, Arumugam; Raja, Pandian B. (Current Organic Chemistry, 2023)
A potent, eco-friendly approach for converting 2,6-arylpiperidin-4-ones into their corresponding oximes in the presence of hydroxylamine hydrochloride and catalysed by nanosize sulfated titania (TiO2/SO42-) solid superacid was developed. Sol-gel method was employed to synthesize the catalyst and confirmed standard characterization techniques viz., by FT-IR, XRD, TEM, SEM, and EDS analysis. After adding 0.05 g of catalyst, the reaction was carried out under stirring in an oil bath at 130°C for 3-7 min under solvent-free conditions. This approach has advantages like catalyst recyclability, high yields, shorter reaction time, and simple work-up. Additionally, the catalyst TiO2/SO42- exhibited good stability, recoverability, and reusability for five consecutive runs without tremendous loss in its catalytic activity. The compounds 3a-o were characterised by IR, 1H and 13C NMR spectral analysis. The coupling constant values in NMR results suggested that the compounds 3a-o exhibit chair conformation with equatorial orientations with all the substituents. This is in agreement with the X-ray crystallography of 3c, confirming that the chair conformation of =N-OH group is syn to C-5 and anti to benzyl group at C-3 and hence if forms more stable (E)-configuration of the oxime 3c.
Keywords: eco-friendly approach